Cell division and tissue mechanics. (October 2019) - Godard, Benoit G; Heisenberg, Carl-Philipp
Abstract : The spatiotemporal organization of cell divisions constitutes an integral part in the development of multicellular organisms, and mis-regulation of cell divisions can lead to severe developmental defects. Cell divisions have an important morphogenetic function in development by regulating growth and shape acquisition of developing tissues, and, conversely, tissue morphogenesis is known to affect both the rate and orientation of cell divisions. Moreover, cell divisions are associated with an extensive reorganization of the cytoskeleton and adhesion apparatus in the dividing cells that in turn can affect large-scale tissue rheological properties. Thus, the interplay between cell divisions and tissue morphogenesis plays a key role in embryo and tissue morphogenesis.